ANALISIS RASIO PROFITABILITAS DAN RASIO LIKUIDITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT BUMI RESOURCES MINERALS Tbk PERIODE 2012-2021 - Nurfadila; Octovian, Reza (Journal of Research and Publication Innovation, 2024)
This study aims to analyze profitability ratios and liquidity ratios to measure financial performance at PT Bumi Resources Mineral Tbk for the 2012-2021 period. The research method used is quantitative with descriptive and comparative research types. The data used comes from PT Bumi Resources Minerals Tbk's 2012–2021 financial statements using financial ratio analysis consisting of profitability ratios and liquidity ratios to assess the company's financial performance. The results showed that the average profitability ratio (Return On Assets -9.99% and Return On Equity -16.05%) was below industry standards, meaning that the company was judged by profitability ratios in an unhealthy state. And for the average yield the liquidity ratio (Current Ratio 72.29% and Cash Ratio 9.74%) is below industry standards, which means that the liquidity ratio in this company is also considered to be in an unhealthy state.